The effect of single-child couples' education based on the theory of planned behavior on their intention to have next child - Mina Sahraei; Shahnaz Kohan; Zahra Mohebbi-Dehnavi; Mahshid AbdiShahshahani (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: In today's society, for many reasons, families have tended toward selective single-child upbringing. Single-child couples' decisions about continuing to have children depend on their attitudes about the consequences of having the next child, perceived norms about it, and perception of control over childbearing behavior. Therefore, this study was conducted with the aim of determining the effect of single-child couples' education based on the theory of planned behavior on their intention to have next child. MATERIALS AND METHODS: This study is a field trial that was conducted in 2022. Eight girls' and boys' primary schools in Golpayegan City, Isfahan Province, were randomly selected for sampling the intervention and control groups. Parents of 70 first-grade students who were single children were selected and placed in groups. 35 couples in the intervention group received education about parenting based on the constructs of the theory of planned behavior during 4-weekly sessions. The questionnaire for the evaluation of childbearing behavior intention was completed by the research samples before the intervention, immediately, and three months after the intervention. Data were analyzed using analysis of variance (ANOVA), independent-samples t-test, and Mann-Whitney statistical tests. RESULT: Demographic and fertility characteristics were homogeneous in the intervention and control groups. The results showed that the changes in the average score of the attitude toward childbearing (P = 0.004), abstract norms (P = 0.001), perceived behavioral control (P = 0.01), behavioral intention (P = 0.003), and the overall score for the evaluation of childbearing behavior intention (P = 0.001) were significant in the intervention group. Comparing the intervention and control groups, the abstract norms immediately after the intervention (P = 0.002) and three months after the intervention (P = 0.002), behavioral intention immediately after the intervention (P = 0.006) and three months after the intervention (P = 0.009), and the overall score of the questionnaire to evaluate the intention to have children immediately after the intervention (P = 0.004) and three months after the intervention (P = 0.008) had significant differences. However, the two groups did not have significant differences in the dimensions of attitude toward having children and perceived behavioral control, immediately and 3 months after the intervention. CONCLUSION: The results obtained from this study showed that parenting education based on the theory of planned behavior generally improved couples' intention to have children, abstract norms, and also the intention to have children later, but it had no effect on the attitude of couples toward having children and controlling their perceived behavior in having children. It seems that couples having only one child are rooted in environmental conditions, such as the economic and social status of society, rather than being under the control and desire of the couple. Therefore, other environmental conditions should also be taken into consideration in fertility promotion policies. Adaptation and implementation of theory of planned behavior (TPB)-based intervention by health policymakers and healthcare providers achieve a better understanding of childbearing.